Varied origins of up-bending breaks in galaxy disks - Aaron E. Watkins; Jarkko Laine; Sébastien Comerón; Joachim Janz; Heikki Salo (EDP SCIENCES S A, 2025)
Aims. Using a sample of 175 low-inclination galaxies from the S(4)G, we investigate the origins of up-bending (Type III) breaks in the 3.6 mu m surface brightness profiles of disk galaxies.
Methods. We reanalyzed a sample of previously identified Type III disk break-hosting galaxies using a new, unbiased break-finding algorithm, which uncovered many new, sometimes subtle disk breaks across the whole sample. We classified each break by its likely origin through close examination of the galaxy images across wavelengths, and compare samples of galaxies separated by their outermost identified break types in terms of their stellar populations and local environments.
Results. We find that more than half of the confirmed Type III breaks in our sample can be attributed to morphological asymmetry in the host galaxies. As these breaks are mostly an artifact of the azimuthal averaging process, their status as physical breaks is questionable. Such galaxies occupy some of the highest density environments in our sample, implying that much of this asymmetry is the result of tidal disturbance. We also find that Type III breaks related to extended spiral arms or star formation often host down-bending (Type II) breaks at larger radius which were previously unidentified. Such galaxies reside in the lowest density environments in our sample, in line with previous studies that found a lack of Type II breaks in clusters. Galaxies occupying the highest density environments most often show Type III breaks associated with outer spheroidal components.
Conclusions. We find that Type III breaks in the outer disks of galaxies arise most often through environmental influence: either tidal disturbance (resulting in disk asymmetry) or heating through, for example, galaxy harrassment (leading to spheroidal components). Galaxies hosting the latter break types also show bimodal distributions in central g - r color and morphological type, with more than half of such galaxies classified as Sa or earlier; this suggests these galaxies may be evolving into early-type galaxies. By contrast, we find that Type III breaks related to apparently secular features (e.g., spiral arms) may not truly define their hosts' outer disks, as often in such galaxies additional significant breaks can be found at larger radius. Given this variety in Type III break origins, we recommend in future break studies making a more detailed distinction between break subtypes when seeking out, for example, correlations between disk breaks and environment, to avoid mixing unlike physical phenomena.